Peptidergic Cell-Specific Synaptotagmins in Drosophila: Localization to Dense-Core Granules and Regulation by the bHLH Protein DIMMED - Park, Dongkook (Society for Neuroscience, 2014)
Bioactive peptides are packaged in large dense-core secretory vesicles, which mediate regulated secretion by exocytosis. In a variety of tissues, the regulated release of neurotransmitters and hormones is dependent on calcium levels and controlled by vesicle-associated synaptotagmin (SYT) proteins. Drosophila express seven SYT isoforms, of which two (SYT-α and SYT-β) were previously found to be enriched in neuroendocrine cells. Here we show that SYT-α and SYT-β tissue expression patterns are similar, though not identical. Furthermore, both display significant overlap with the bHLH transcription factor DIMM, a known neuroendocrine (NE) regulator. RNAi-mediated knockdown indicates that both SYT-α and SYT-β functions are essential in identified NE cells as these manipulations phenocopy loss-of-function states for the indicated peptide hormones. In Drosophila cell culture, both SYT-α and neuropeptide cargo form DIMM-dependent fluorescent puncta that are coassociated by super-resolution microscopy. DIMM is required to maintain SYT-α and SYT-β protein levels in DIMM-expressing cells in vivo. In neurons normally lacking all three proteins (DIMM(−)/SYT-α(−)/SYT-β(−)), DIMM misexpression conferred accumulation of endogenous SYT-α and SYT-β proteins. Furthermore transgenic SYT-α does not appreciably accumulate in nonpeptidergic neurons in vivo but does so if DIMM is comisexpressed. Among Drosophila syt genes, only syt-α and syt-β RNA levels are upregulated by DIMM overexpression. Together, these data suggest that SYT-α and SYT-β are important for NE cell physiology, that one or both are integral membrane components of the large dense-core vesicles, and that they are closely regulated by DIMM at a post-transcriptional level.